2020
DOI: 10.1039/d0tc00301h
|View full text |Cite
|
Sign up to set email alerts
|

N2 positively charged defects in diamond. A quantum mechanical investigation of the structural, electronic, EPR and vibrational properties

Abstract: Structural, EPR and vibrational characterization of the N2, N+2 and N++2 defects in diamond from ab initio quantum-mechanical calculations with the CRYSTAL code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Recent applications to various defects (substitutional N, or Ns, 31 VN − 2 , 32 N + 2 33 ) have confirmed that the present approach is able…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Recent applications to various defects (substitutional N, or Ns, 31 VN − 2 , 32 N + 2 33 ) have confirmed that the present approach is able…”
Section: Introductionsupporting
confidence: 61%
“…It was designed to better describe the core electrons, but the valence shells are also richer, with exponents of the most diffuse s and p functions of C and N set to 0.169 bohr −2 and 0.212 bohr −2 , respectively. 37 This combination of the B3LYP functional and the 6-31G-J * basis set has been shown to provide accurate results for the EPR data of three defects in diamond, namely, Ns, 31 VN − 2 (the negatively charged form of VN 2 , with two nitrogen atoms around a vacancy), 32 and N + 2 , the positively charged form of the so called A defect (two vicinal substitutional N atoms), 33 where in all three cases, the spin state is a doublet.…”
Section: Methodsmentioning
confidence: 98%
“…Chem. Phys., 2022, 24, 12950-12960 | 12959 (substitutional nitrogen), 31 VN 2 À (negatively charged, with a vacancy and two nitrogen atoms as first neighbors) 32 or N 2 + (two vicinal substitutional nitrogen atoms, positively charged) 33 defects in diamond, that can be compared with experimental EPR results (see for example ref. [34][35][36][37]; (b) In determining the stability of the AFM phases with respect to the FM one in TM compounds, through the superexchange mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by a previous paper, the combined use of the B3LYP functional and the triple ζ basis set [20][21][22][23][24][25][26] provides very accurate results for the vibrational spectra, in terms of both wavenumbers and intensities [25,[27][28][29][30][31]. The exchange and Coulomb infinite lattice series can be modified through five parameters, T i , which were set to 8 (T 1 -T 4 ) and 16 (T 5 ).…”
Section: Methodsmentioning
confidence: 99%